Horyzont kresu. Glosy do Drugiego przyjścia Williama Butlera Yeatsa - Próchniak, Paweł (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-ansi-language: EN-US; mso-fareast-theme-font: minor-fareast; mso-fareast-language: PL; mso-bidi-language: AR-SA;" lang="EN-US">The outline presents a comprehensive interpretation of the poem The Second Coming by William Butler Yeats.